2014
DOI: 10.1021/cn500096g
|View full text |Cite
|
Sign up to set email alerts
|

Mice Genetically Depleted of Brain Serotonin Do Not Display a Depression-like Behavioral Phenotype

Abstract: Reductions in function within the serotonin (5HT) neuronal system have long been proposed as etiological factors in depression. Serotonin selective reuptake inhibitors (SSRIs) are the most common treatment for depression and their therapeutic effect is generally attributed to their ability to increase the synaptic levels of 5HT. Tryptophan hydroxylase 2 (TPH2) is the initial and ratelimiting enzyme in the biosynthetic pathway of 5HT in the CNS and losses in its catalytic activity lead to reductions in 5HT prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 97 publications
1
32
0
Order By: Relevance
“…Yet, it should be noted that depression does not always manifest in mice as expected, a relevant example being mice with targeted deletion of serotonin production in the brain. These mice show impaired maternal care (Angoa‐Perez et al ), but no signs of depression (Angoa‐Perez et al ), even though selective serotonin reuptake inhibitors (SSRIs) are the most widely used pharmacotherapy for treating PPD (De Crescenzo et al ). Thus, our results do not rule out a connection between the impaired maternal care observed in Hp1bp3 −/− mice and PPD in humans, but exclude cholinergic imbalance as a cause for such symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it should be noted that depression does not always manifest in mice as expected, a relevant example being mice with targeted deletion of serotonin production in the brain. These mice show impaired maternal care (Angoa‐Perez et al ), but no signs of depression (Angoa‐Perez et al ), even though selective serotonin reuptake inhibitors (SSRIs) are the most widely used pharmacotherapy for treating PPD (De Crescenzo et al ). Thus, our results do not rule out a connection between the impaired maternal care observed in Hp1bp3 −/− mice and PPD in humans, but exclude cholinergic imbalance as a cause for such symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, dietary tryptophan depletion increases killing behavior that is ameliorated by boosting brain serotonin levels (45, 46). Mutant mice that have a nonfunctional or deleted tph2 , and thus have no serotonin synthesis in the brain, display exaggerated aggressive behavior and compulsive behavior compared with control mice (4749). These data provide evidence that serotonin deficiency in the brain leads to magnified aggression.…”
Section: Role Of Serotonin In Neuropsychiatric Illnessmentioning
confidence: 99%
“…Although antidepressant drugs elevate monoamine concentrations in the brain less than 30 min after administration (Yoshitake et al, 2003), administration for several weeks is required for their therapeutic effects to occur (Gelenberg and Chesen, 2000). In addition, another study has demonstrated that tryptophan hydroxylase 2 knock-out mice that were depleted of serotonin in the brain did not display the depression-like behavioral phenotype (Angoa-Pérez et al, 2014). Therefore, the other systems need to be examined to explain the pathogenesis of major depression.…”
Section: Introductionmentioning
confidence: 99%